2017
DOI: 10.1016/j.jcma.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Association between sociodemographic, psychosocial, lifestyle factors, and self-reported health among migrant laborers in China

Abstract: Our investigation indicated that there are many factors associated with SRH. In particular, this study undertook a comprehensive investigation of the associations between sociodemographic, psychosocial, lifestyle factors, and SRH in China, the results of which could better inform medical researchers and governments from a Chinese perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…For example, factors influencing poor self-reported health of internal Chinese migrant labourers were associated with age, working hours, marital status, illness and hospitalization. Factors associated with good self-reported health included income, number of friends, levels of trust, education and appropriate alcohol consumption (38). Long working hours and income dissatisfaction were associated with poor mental health among rural-urban migrants in Guangzhou, China, while higher income and social support were associated with reduced risk (39).…”
Section: Health Issues and Outcomes Associated With Migrationmentioning
confidence: 97%
“…For example, factors influencing poor self-reported health of internal Chinese migrant labourers were associated with age, working hours, marital status, illness and hospitalization. Factors associated with good self-reported health included income, number of friends, levels of trust, education and appropriate alcohol consumption (38). Long working hours and income dissatisfaction were associated with poor mental health among rural-urban migrants in Guangzhou, China, while higher income and social support were associated with reduced risk (39).…”
Section: Health Issues and Outcomes Associated With Migrationmentioning
confidence: 97%
“…Li et al found that money earned from employment, the number of friends a person has, and the quality of their neighbour relationships were significant factors in self-reported good health (Li, Meng et al, 2017).…”
Section: Additional Positive Mental Health Factors Highlighted In Thementioning
confidence: 99%
“…Wang et al particularly emphasize the need for prior awareness of the discrimination urban migrants may subsequently suffer at their destination (Wang, Li et al, 2010). (Wen, Zheng et al, 2017) One intriguing finding from Li et al was that respondents who consumed alcohol were more likely to report good health: most other previous studies have usually found alcohol consumption to be associated with poor self-reported health (Li, Meng et al, 2017).…”
Section: Additional Positive Mental Health Factors Highlighted In Thementioning
confidence: 99%
“…The rapid industrialization, in particular in the eastern coastal region, attracted large scales of population internal migration [ 12 ]. The population of internal migrants increased from about 6 million in the 1980s to 244 million in 2017, accounting for about 18% of the population size nowadays in China [ 13 , 14 ]. The majority of internal migrants occupied job positions that would not otherwise be filled by the locals [ 15 ], making a great contribution to the economic development in China over the past few decades [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This makes transfer of insurance enrollment across different funds and regions extremely challenging, if not impossible. Meanwhile, medical services outside of local contracted providers usually attract higher levels of out-of-pocket payments [ 1 ], jeopardizing the accessibility of healthcare services of internal migrants [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%